Effects of Reduced Substrate Volumetric Water Contents on the Morphology and Physiology of Three Landscape Shrubs Grown in a Greenhouse - Ji-Jhong Chen; Youping Sun (HortScience)
Reduced precipitation and increasing temperatures caused by climate change have escalated the irrigation requirements for maintaining the aesthetic quality of urban landscape plants. Many cities in the western United States now mandate the incorporation of drought-tolerant plants in new landscapes because of concerns regarding water scarcity. However, a knowledge gap persists regarding the drought tolerance of ornamental plant species commonly used in urban landscapes. The objectives of this study were to determine the effects of decreased volumetric water contents on the morphology, physiology, and plant growth of Rosa ×hybrida ‘Meibenbino’ (Petite Knock Out® rose), Salvia rosmarinus ‘Arp’ (‘Arp’ rosemary), and Vitex agnus-castus ‘SMVACBD’ (Blue Diddley® chaste tree). Twenty-four plants of each species were randomly assigned to an automated irrigation system, and the substrate volumetric water content was maintained at 0.40 or 0.20 m3⋅m−3 for 50 days. As the substrate volumetric water content declined, plants exhibited an increase in the proportion of visibly wilted and damaged leaves as well as chlorosis. Rose, rosemary, and vitex experienced up to a 30% decrease in the plant growth index [(height + width 1 + width 2)/3], whereas leaf dry weights (DWs) decreased by 84%, 66%, and 58%, respectively. Landscape plants in this study acclimated to drought stress by reducing the total leaf area, developing small leaves, increasing the root-to-shoot ratio, and decreasing stomatal conductance. However, stomatal closure also led to increases in leaf temperatures because of limited transpirational cooling efficiency. For the rosemary, trichome density on the adaxial surface increased as the substrate volumetric water content decreased. The trichome density might be regulated by turgor-pressure-driven cell expansion because the trichome density decreased with the increased leaf width. Rose was sensitive to decreased substrate water availability, resulting in severe growth reduction with a high leaf–air temperature difference. Rosemary maintained better visual quality than that of rose, but the low root-to-shoot ratio resulted in a high leaf-air temperature difference. Vitex, which had the highest root-to-shoot ratio, exhibited the lowest canopy–air temperature and lower growth reduction. Overall, under the experimental conditions, S. rosmarinus ‘Arp’ and V. agnus-castus ‘SMVACBD’ showed better tolerance to drought stress compared with that of R. ×hybrida ‘SMVACBD’.